Transformasi informatika: kecerdasan buatan sebagai partner belajar di tengah kesenjangan akses digital - Annur, Zulfadhli (Maliki Interdisciplinary Journal, 2026)
The rapid growth of digital technology in the globalization era has accelerated the use of artificial intelligence (AI) in education, including Informatics Engineering programs that require adaptive, data-driven learning. This article examines the role of AI as a learning partner for informatics students and explores how unequal digital access shapes the fairness of its implementation. Using a literature review approach, the study synthesizes research on AI-based learning systems in Islamic Religious Education, Arabic language education, and secondary education, and then relates these findings to the informatics context. The review shows that tools such as chatbots, intelligent tutoring systems, and adaptive learning platforms can improve evaluation efficiency, personalize learning materials, and strengthen student motivation and autonomy. However, limited infrastructure, uneven digital literacy, and unresolved ethical issues regarding data privacy and algorithmic bias may widen the digital divide between well-resourced institutions and schools in remote or underdeveloped regions. These results underline the need for equitable infrastructure development, systematic digital literacy training, and clear ethical guidelines so that AI can function as an inclusive and just learning partner in Informatics Engineering.